Waiting for answer This question has not been answered yet. You can hire a professional tutor to get the answer.

# How do I convert the equation ##f(x)=x^2-2x-3## to vertex form?

##color(red)( f(x) = (x-1)^2-4)##

The vertex form of a quadratic is given by ##y = a(x – h)^2 + k##, where (##h, k##) is the vertex.

The "##a##" in the vertex form is the same "##a##" as in ##y = ax^2 + bx + c##.

Your equation is

##f(x) = x^2-2x-3##

We convert to the "vertex form" by .

**Step 1.** Move the constant to the other side.

##f(x)+3 = x^2-2x##

**Step 2.** Square the coefficient of ##x## and divide by 4.

##(-2)^2/4 = 1##

**Step 3.** Add this value to each side

##f(x)+3+1 = x^2-2x+1##

**Step 4.** Express the right hand side as a square.

##f(x)+4 = (x-1)^2##

**Step 5.** Isolate ##f(x)##.

##f(x) = (x-1)^2-4##

The equation is now in vertex form.

##y = a(x – h)^2 + k##, where (##h, k##) is the vertex.

##h = 1## and ##k = -4##, so the vertex is at (##1,-4##).